Systemic racism and undocumented Latino migrant laborers during COVID-19: A narrative review and implications for improving occupational health - Juan L. Salinas; Manisha Salinas (Elsevier, 2022)
Background: Systemic racism is built upon the racial exploitation of minorities and has been further exposed inequalities amidst the COVID-19 global pandemic. The historic reliance of undocumented migrant Latino laborers continues to influence the modern-day work conditions Latinos face such as low wages, limited benefits, and an emphasis on productivity over safety, which also increases their risk for adverse health outcomes. Objective: This narrative review aims to describe and highlight key risk factors on the impact of systemic racism and how it shapes the work and occupational health experiences of Latino laborers in the US, as well as strategies to overcome barriers. Method: In this review, we explore empirical studies, news reports, and policy briefs that highlight the social factors impacting occupational health outcomes for undocumented Latino migrant laborers and synthesize the information to report major challenges experienced during the pandemic and propose recommendations for improving conditions and occupational health of these groups. Results: Existing literature demonstrated that (1) documentation status was a barrier to federal relief programs during COVID-19; (2) though categorized as essential workers, workplace conditions were harmful towards preventing infection and transmission of COVID-19; and (3) there was an increased burden particularly for undocumented Latino women both in the workplace and at home during the pandemic. Recommendations include prioritization of undocumented immigrants in government relief, and addressing both individual and environmental level stressors in the workplace to promote inclusivity and reduce unnecessary suffering of Latino migrant workers. Conclusion: Latino laborers should be treated with dignity and respect with workplace protections as they are designated as essential workers during the COVID-19 pandemic.